Hubungan Aktivitas Fisik, Konsumsi Rokok, Konsumsi Lemak dan Literasi Kesehatan dengan Derajat Hipertensi - Azizah Syah Putri; Izza Suraya (Politeknik Baubau, 2024)
Hypertension is still a problem that occurs in the community. According to data from the North Larangan Health Center, hypertension ranks first in non-communicable disease health problems with a prevalence of hypertension in 2022 of 34%. This study aims to determine the relationship between physical activity, cigarette consumption, fat consumption and health literacy with the degree of hypertension in the North Larangan Health Center in 2023. This type of research is analytic quantitative research using a cross sectional study design. The population in this study were patients with hypertension at the North Larangan Health Center, Tangerang City. The sample was selected using purposive sampling technique with a total sample size of 115 respondents. Data collection was carried out during April - May 2023 by interview method using a questionnaire instrument. Data were analyzed univariately and bivariate with the Chi-Square test. The results of univariate analysis showed that most respondents with grade II hypertension (50.4%), age ≥45 years (58.3%), male gender (53%), less physical activity (58.3%), smoking consumption (39.1%), high fat consumption (60%) and not enough health literacy (50.4%). The results of bivariate analysis showed a variable relationship between physical activity (p-value=0.030), cigarette consumption (p-value=0.027), fat consumption (p-value<0.001), and health literacy (p-value<0.001) with the degree of hypertension. This it can be concluded that there is a relationship between physical activity, cigarette consumption, fat consumption and health literacy with the degree of hypertension in hypertensive patients at the North Larangan Health Center in 2023. It is expected that people with hypertension can carry out physical activity habits, avoid smoking habits, reduce high fat consumption and know information and understand health literacy for themselves.